Artikel Review: Tingkat Kepatuhan dan hal - hal yang yang Mempengaruhi Kepatuhan dalam Penggunaan Obat Antibiotik: Review Article: Level of Complaince and Things Impacting Compliance in Antibiotic Drug Use - Indah Laily Hilmi; Salman Salman; Sridevi Anggraini (Jurnal Surya Medika (JSM), 2023)
Infectious diseases are still an important health problem in Indonesia, especially in developing countries. Antibiotics are drugs that are often used as a treatment for infectious diseases caused by bacteria with a mechanism of action by killing or inhibiting the growth of bacteria and with relatively little toxicity to humans. The use of antibiotics must be used rationally if used correctly it will reduce the level of antibiotic resistance. Antibiotic resistance is a condition where the inability of antibiotics to fight bacteria due to bacterial mutations. Cases of resistance reported by the Deputy Minister of Health of the Republic of Indonesia, the prevalence of antibiotic resistance continues to increase. Compliance with the use of antibiotic drugs is an effort to overcome the prevention of resistance in patients receiving antibiotic therapy, by knowing several factors related to patient adherence including demographic factors, belief behavior factors, drug information giving factors and counseling factors.